Marine Resources for Marine-Derived Drugs: A Review - Supanekar, Santosh P.; Naik , Mayur S.; Sarwade, Varun V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The oceans are the world’s most important sources of biological activity, water, and biomass production. They supply food, oxygen, and other natural products critical for human existence, and interactions between the oceans and the climate. The oceans serve as the world’s greatest reservoir of biodiversity, including marine mammals, fish, crustaceans, molluscs, and countless species of zoophytoplankton. The ocean is a key source of organisms that are beginning to provide new and potent drugs for the treatment of human disease, as well as new products that use in biotechnology. Ocean can support human health, through providing new sources of drugs to treat human disease. Bioactive metabolites derived from marine organisms provide a rich source of chemical diversity that can contribute to design and development of new and potentially useful pharmaceutical agents. The marine ecosystem possesses efficient pharmaceutical materials to identify, isolate and characterize new compounds suitable for therapeutic purposes. Marine sponges, tunicates, fishes, soft corals, nudibranchs, sea hares, molluscs, echinoderms, bryozoans, prawns, shells, sea slugs, and marine microorganisms are sources of bioactive compounds. The current review is designed to collate all currently available data about the marine drugs with respect to sources, classification, chemical classes, metabolites of marine algae, fungi, bacteria and invertebrates, techniques for separation and isolation, and examples. This review aims to provide a holistic, multidisciplinary account of the current state of affairs on this topic.